Mitogenomics of the extinct cave lion, Panthera spelaea (Goldfuss, 1810), resolve its position within the Panthera cats - Larson, G; Barnett, R; Mendoza, M; Soares, A; Ho, S; Zazula, G; Yamaguchi, N; Shapiro, B; Kirillova, I; Gilbert, M (Ubiquity Press, 2016)
The extinct cave lion (Panthera spelaea) was an apex predator of the Pleistocene, and one of the largest felid species ever to exist. We report the first mitochondrial genome sequences for this species, derived from two Beringian specimens, one of which has been radiocarbon dated to 29,860 ± 210 14C a BP. Phylogenetic analysis confirms the placement of the cave lion as the sister taxon to populations of the modern lion (P. leo). Using newly recovered stem pantherine fossils to calibrate a molecular clock, we estimate that P. spelaeaand P. leodiverged about 1.89 million years ago (95% credibility interval: 1.23–2.93 million years), highlighting the likely position of this extinct carnivore as a distinct species.